Adverse Effects on the Postoperative Urinary Function After Combined Resection of Inferior Vesical Artery in Laparoscopic Lateral Pelvic Lymph Node Dissection: Retrospective Analysis of Consecutive 95 Series. Issue 6 (December 2019) - Manabe, Tatsuya; Koga, Yasuo; Kubo, Hiroshi; Baba, Koichi; Nagayoshi, Kinuko; Nagai, Shuntaro; Ueki, Takashi; Nakamura, Masafumi; Noshiro, Hirokazu
Abstract : Background: The combined resection of the vesical artery (VA) in laparoscopic lateral pelvic lymph node dissection (L-LPLD) was reported to facilitate the safe dissection of metastatic lymph nodes. However, whether or not the combined VA resection affects the urinary function remains controversial. Purpose: The purpose of the present study was to examine the risk factors for the postoperative urinary dysfunction (PUD) after L-LPLD followed by total mesorectal excision and to clarify the effects of the combined VA resection in L-LPLD on PUD. Patients and Methods: L-LPLD was performed in 95 patients with advanced rectal cancer at Saga University Hospital and Kyushu University Hospital from January 2013 to December 2017. The risk factors for PUD after L-LPLD were investigated. Results: The univariate analysis revealed that the combined resection of the inferior vesical artery (IVA) was a risk factor for PUD. To examine by the type of IVA resection, the incidence of PUD significantly increased with the bilateral IVA resection, but the unilateral IVA resection induced PUD on the same level with the preservation of IVA. Conclusions: Bilateral IVA resection in L-LPLD could increase the incidence of PUD. Thus, if possible, the preservation of the unilateral IVA through L-LPLD should be considered.